2011
DOI: 10.1246/cl.2011.1165
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-catalyzed Oxidative Alkenylation of Arenes via Regioselective C–H Bond Cleavage Directed by a Nitrogen-containing Group

Abstract: Direct alkenylation of 1-phenylpyrazoles with alkenes such as acrylates accompanied by regioselective C–H bond cleavage proceeds efficiently under ruthenium catalysis in the presence of a copper oxidant. The procedure is also applicable to 2-phenylbenzothiazole and benzanilide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(22 citation statements)
references
References 75 publications
1
20
0
1
Order By: Relevance
“…In the area of material science, the phenol motif plays a crucial role for the construction of poly(phenol ethers) or their modification to adjust their macroscopic properties, such as their melting or glass-transition temperatures, for specific applications. [5] The catalytic system, consisting of [{Ru(p-cymene)Cl 2 } 2 ] (5 mol %) and Cu(OAc) 2 (2 equiv) as the co-oxidant enabled the efficient coupling of the biaryl moiety with common acrylates. [2] Evidently, C À H functionalization plays a more and more important role in method development as disadvantages, such as prefunctionalization with halogens or reactivity problems with lighter halogens, have been overcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the area of material science, the phenol motif plays a crucial role for the construction of poly(phenol ethers) or their modification to adjust their macroscopic properties, such as their melting or glass-transition temperatures, for specific applications. [5] The catalytic system, consisting of [{Ru(p-cymene)Cl 2 } 2 ] (5 mol %) and Cu(OAc) 2 (2 equiv) as the co-oxidant enabled the efficient coupling of the biaryl moiety with common acrylates. [2] Evidently, C À H functionalization plays a more and more important role in method development as disadvantages, such as prefunctionalization with halogens or reactivity problems with lighter halogens, have been overcome.…”
mentioning
confidence: 99%
“…The group of Satoh and Miura showed that pyrazole is a suitable directing group (DG) for the ortho olefination of 1-phenylpyrazoles. [5] The catalytic system, consisting of [{Ru(p-cymene)Cl 2 } 2 ] (5 mol %) and Cu(OAc) 2 (2 equiv) as the co-oxidant enabled the efficient coupling of the biaryl moiety with common acrylates. The use of large amounts of copper salts is a general feature of these types of reactions as the in situ generated metal complex needs to be reoxidized first before the next catalytic cycle can be started.…”
mentioning
confidence: 99%
“…Quite interestingly, the first example on the ruthenium‐catalyzed, cross‐dehydrogenative coupling of alkyl acrylates was reported recently and employed benzo[ b ]furan‐2‐carboxylate derivatives as substrates 11. The scope of this ruthenium‐catalyzed, cross‐dehydrogenative coupling of alkyl acrylates has rapidly expanded to various other aryl/heteroaryl systems by using directing groups other than carboxylate 4ho. Despite the widespread application in dehydrogenative couplings, surprisingly, a Ru‐catalyzed alkylation with acrylates via CH activation has not yet been documented 12.…”
Section: Optimization Of Reaction Conditions For Directed Hydroarylatmentioning
confidence: 99%
“…Initial exploratory experiments were carried out by using benzo[ b ]furan 1 a as the substrate and methyl acrylate 2 a as an acceptor (Table 1). In general, the cationic ruthenium complexes in combination with an oxidant, have been used for the alkenylations 4ho. In anticipation of the requisite alkylation, various neutral ruthenium complexes have been explored in this pursuit by using adamantane‐1‐carboxylic acid (AdCO 2 H) as an additive.…”
Section: Optimization Of Reaction Conditions For Directed Hydroarylatmentioning
confidence: 99%
“…In recent years, the functionalisation of unreactive ortho arene CH bonds1 through transition‐metal‐catalysed directing‐group (DG) assisted strategies2 has been the subject of a number of intense investigations. Although numerous DGs comprising carboxylic,3ad ester,3e carbonyl,3fg sulfoximine,3hi phosphinoxy,3j nitroso,3k ether,3l and heterocycle3mo derivatives have been employed for regioselective arene CH olefination, reports involving the generation of a DG in situ and its transformation are scarce 4…”
Section: Introductionmentioning
confidence: 99%